An Evaluation of Foreign Direct Investment in India - Saxena, Kavita (Journal of Commerce and Trade, 2014)
FDI benefits domestic industry as well as the consumers by providing opportunities for technological upgradation, access to global managerial skills and practices, optimal utilization o human and natural resources, making Indian industry internationally competitive, opening of export market, providing backward and forward linkages and access to international quality goods and services. It is most important that FDI is central for India’s integration into global production chain, which involves production by multinational corporations spread across locations ail over the world. Liberalization policies have led to rapid growth in FDI flows in recent years. Basing on the benefits associated with FDI several developing; as well developed countries complete to a high degree for FDI. Foreign capital is considered as an important element in the path of development process in India. FDIs have created tremendous opportunity for India’s development and helped to boost the performance of local firms as well as the globalization of some of them. This has undeniably raised India’s stature among developing countries. India needs massive investments to sustain high- quality economic growth, particularly in the energy and infrastructure sectors. Policy makers are looking at FDI on its own is not a panacea for rapid growth and development. What India needs is to put in place a comprehensive development strategy, which includes being open to trade and FDI. This should go a long way in fulfilling the ultimate goal of permanently eradicating poverty.